Tibiotalocalcaneal arthrodesis in a rare case of tuberculosis of the talus - Chiara Comis; Tommaso Greco; Michele Inverso; Antonio Mascio; Chiara Polichetti; Marco Barbaliscia; Vincenzo La vergata; Massimiliano Mosca; Silvio Caravelli; Nicola Mondanelli; Elisa Troiano; Giulio Maccauro; et al. (Medicinski glasnik, 2023)
Aim: To assess our personal experience of a case of tuberculosis of the talus, and to provide an overview of the literature about this tuberculosis manifestations, including all its aspects: epidemiology, clinical and imaging presentation, and all the treatments available to the current state of knowledge. Methods: We present our experience in a case of a 34-year-old patient, who came to our attention with difficulty in walking and pain due to a talar tuberculosis, with consequent bone disruption and reabsorption, and foot deformities. Results: A tibiotalocalcaneal arthrodesis with retrograde nail and bone graft was performed after antibiotic therapy. Today, almost two years after treatment, the patient can walk independently with no major limitations in everyday life. Conclusion: Tibiotalocalcaneal arthrodesis with bone graft showed good functional results in this case study, with complete graft fusion and good functional and radiological outcomes.
Keywords: chronic ankle disease; foot disease; tarsal bones; tibiotalocalcaneal arthrodesis; foot deformities